Closed-form solutions of stress intensity factors for semi-elliptical surface cracks in a cylindrical bar under pure tension - Ramezani, M. K. (Springer, 2022)
In this work, the stress intensity factors (SIFs) for a wide range of semi-elliptical surface cracks with different inclination angles in a cylindrical bar subjected to pure tension were investigated numerically. The main parameters considered to evaluate the SIFs were the crack size ratio (a/d), the crack aspect ratio (a/c), and the crack inclination angle (theta). The dual-boundary element method implemented in software BEASY was used to compute the SIF values for cracks. Furthermore, the general closed-form solutions were proposed to evaluate the corresponding SIFs for Mode I, Mode II and Mode III types of fracture through curve fitting approaches. These solutions can provide accurate and reliable values of stress intensity factors for a crack on a cylindrical bar under pure tension in a rapid way compared to those obtained using computational models. In addition, these results can be used as inputs for failure studies and life evaluations of cracked cylinder under working conditions.